MIOCENE LARGER FORAMINIFERAL BIOSTRATIGRAPHY IN THE MEDITERRANEAN AND THE INDO-PACIFIC AREAS - Bolivar Feriche, Monica (Università degli studi di Ferrara, 2022)
Larger benthic foraminifera (LBF) constitute an outstanding tool for biostratigraphic, palaeoecological and palaeobiogeographic studies because of their widespread geographical distribution, fast evolutionary changes, high susceptibility to environmental changes, and high abundance in the sedimentary successions. The PhD project dealt with Miocene LBF (alveolinoids, austrotrillinids, lepidocyclinids and nummulitids) newly recorded in the Mediterranean (southeastern Spain) and Indo-Pacific areas (Indonesia, northern Philippine sea, the Maldives and Ryukyu Islands). The new LBF record from the Sierra de Marmolance (Granada province, southeasrtern Spain) belongs to a 270-m thick continuous and in situ limestone succession of middle Miocene age (dated by the occurrence of Langhian–Serravallian planktonic foraminifera at the bottom of the succession). The LBF assemblage is represented by Austrotrillina brunni, Austrotrillina striata, Borelis inflata, Eulepidina formosoides, Eulepidina ex.interc dilatata et formosoides, Heterostegina assilinoides, Neorotalia viennoti, Nephrolepidina ex.interc. morgani et praemarginata, Nephrolepidina tournoueri, Nummulites fichteli, Nummulites kecskemetii, Nummulites vascus, Operculina complanata, Risananeiza crassaparies and Spiroclypeus sp. These species, up to now considered indicative of Rupelian–Chattian and Aquitanian–Burdigalian, extend their time ranges from the Rupelian to the early Serravallian. Since they are considered as Neogene biochronostratigraphic markers, this study highlights the need of a substantial revision of the Oligocene–Miocene SBZs. The new records of Austrotrillina from Ibi and Sierra de Marmolance (southeastern Spain), Indonesia (Mankalihat and Wailawi) and western Pacific (Kitadaito-jima and Kikai Seamount) allowed to assess their taxonomy according to the shell structure (tectum and a parakeriotheca with subsutural alcoves), biostratigraphy and palaeobiogeography. Austrotrillina eocaenica first appears in the middle–late Eocene of Iran. Two Rupelian ...